2020
DOI: 10.1155/2020/6923103
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Myofibroblastic Tumor: A Rare Presentation and an Effective Treatment with Crizotinib

Abstract: Inflammatory myofibroblastic tumor (IMT) is a rare entity of neoplastic origin. It usually occurs in children and adolescents and most commonly involves pulmonary and gastrointestinal sites. Here, the authors present two cases; one is the nine months old boy with a subcutaneous IMT in the left temporal region that was treated successfully with surgical resection. To the best of our knowledge, this is the first reported case of a subcutaneous IMT in this particular region. The second is an eight years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…ALK inhibitors, such as crizotinib, may be used for IMT. Crizotinib may be used for visceral IMT 2,15,16 . In a phase II clinical trial of patients with advanced, inoperable IMT treated with crizotinib, a 50% objective response rate was observed, supporting its use in this patient population 17 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ALK inhibitors, such as crizotinib, may be used for IMT. Crizotinib may be used for visceral IMT 2,15,16 . In a phase II clinical trial of patients with advanced, inoperable IMT treated with crizotinib, a 50% objective response rate was observed, supporting its use in this patient population 17 …”
Section: Discussionmentioning
confidence: 98%
“…Genomic analysis has shown that 85% of IMT have kinase fusions, involving either ALK , ROS1 , or PDGFRB genes, with a preponderance having the ALK rearrangement 2 . Multiple ALK fusion partners exist, including CLTC , RANBP2 , FN1 , TPM3 , TPM4 , SEC31A , CARS , and TF3 , among others 2,13,15 …”
Section: Discussionmentioning
confidence: 99%
“…Because active ALK gene rearrangements have been identified in 50% of cases, targeted ALK inhibition is a promising treatment option 18 . Khail et al 17 reported that it is safe and effective to use ALK inhibitors like crizotinib for patients with unresectable and recurrent ALK‐1 positive tumors in the pediatric population. Dong et al 18 proposed a treatment based on risk stratification for IMT in a retrospective study of 6 described children.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is well established in resectable lesions, and complete surgical resection with clear margins is associated with a favorable prognosis. 17,18 Hilar tumors can involve the portal vein, hepatic artery and bile duct, and spread to the branches of the portal triad, causing obstructive symptoms, occlusive phlebitis, and portal hypertension. 19 Thus, liver transplantation is an excellent alternative for locally advanced hilar tumors, since it ensures complete tumor resection with free margins (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…A ressecção cirúrgica completa com margens claras está associada a um prognóstico favorável. (4) A radiação também pode ser aplicada em casos recorrentes ou situações de invasão local de órgãos. (5) Apesar das escassas evidências referentes ao tratamento desses tumores em adultos, o Crizotinibe é amplamente utilizado e eficaz em pacientes com câncer de pulmão…”
Section: Ao Editorunclassified